Ending groundwater overdraft without affecting food security - Perez, Nicostrato; Singh, Vartika; Ringler, Claudia; Xie, Hua; Zhu, Tingju; Sutanudjaja, Edwin H.; Villholth, Karen G. (Springer, 2024)
Groundwater development is key to accelerating agricultural growth and to achieving food security in a climate crisis. However, the rapid increase in groundwater exploitation over the past four decades has resulted in depletion and degradation, particularly in regions already facing acute water scarcity, with potential irreversible impacts for food security and economic prosperity. Using a climate–water–food systems modelling framework, we develop exploratory scenarios and find that halting groundwater depletion without complementary policy actions would adversely affect food production and trade, increase food prices and grow the number of people at risk of hunger by 26 million by 2050. Supportive policy interventions in food and water systems such as increasing the effective use of precipitation and investments in agricultural research and development could mitigate most negative effects of sustainable groundwater use on food security. In addition, changing preferences of high-income countries towards less-meat-based diets would marginally alleviate pressures on food price. To safeguard the ability of groundwater systems to realize water and food security objectives amidst climate challenges, comprehensive measures encompassing improved water management practices, advancements in seed technologies and appropriate institutions will be needed.